Rising longevity, increasing the retirement age, and the consequences for knowledge-based long-run growth - Michael Kuhn; Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2020)
We assess the long-run growth effects of rising longevity and increasing the retirement age when growth is driven by purposeful research and development. In contrast to economies in which growth depends on learning-by-doing spillovers, raising the retirement age fosters economic growth. How economic growth changes in response to rising life expectancy depends on the retirement response. Employing numerical analysis we find that the requirement for experiencing a growth stimulus from rising longevity is fulfilled for the United States, nearly met for the average OECD economy, but missed by the EU and by Japan.
urn:nbn:de:bsz:100-opus-17407
Keywords: J10; J26; O30; O41; 330; Demographic Change; Rising Life Expectancy; Pension Reforms; Long-Run Economic Growth; R&D; Innovation